2016
DOI: 10.1021/acssuschemeng.6b01537
|View full text |Cite
|
Sign up to set email alerts
|

Glass-Free CuMoO4 Ceramic with Excellent Dielectric and Thermal Properties for Ultralow Temperature Cofired Ceramic Applications

Abstract: A new glass-free low temperature sinterable CuMoO 4 ceramic was prepared by a solid state ceramic route. The structural, microstructural, electron dispersive spectrum, and X-ray photoelectron spectroscopy analysis revealed the quality of the material synthesized. The CuMoO 4 ceramic sintered at 650 °C exhibits densification of 96% and low coefficient of thermal expansion (CTE) of 4.6 ppm/°C in the temperature range of 25−500 °C. It has relative permittivity (ε r ) of 7.9, quality factor (Qf) of 53 000 GHz, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
61
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 58 publications
7
61
0
Order By: Relevance
“…AMoO 4 (A refers to transition-metal ions) compounds have attracted wide attention because of their thermochromic properties, and have great potential applications in temperature sensors. Among them, CuMoO 4 was most widely studied [1][2][3][4][5]. It was believed that the thermochromic properties of CuMoO 4 originate from the reversible first-order phase transition of α-CuMoO 4 (green) and γ-CuMoO 4 (red-brown) during temperature and pressure change [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMoO 4 (A refers to transition-metal ions) compounds have attracted wide attention because of their thermochromic properties, and have great potential applications in temperature sensors. Among them, CuMoO 4 was most widely studied [1][2][3][4][5]. It was believed that the thermochromic properties of CuMoO 4 originate from the reversible first-order phase transition of α-CuMoO 4 (green) and γ-CuMoO 4 (red-brown) during temperature and pressure change [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…At present, it has been reported that the phase transition temperature can be controlled by doping at A site or B site. Ikuo Yanase et al [11] found that the phase-transition temperature gradually shifted to high temperature with the increase of doping content by replacing Mo with W in CuMoO 4 , while Robertson et al [12] found that the phase-transition temperature shifted to low temperature with the increase of doping content by replacing Co with Mg in CoMoO 4 . Ikuo Yanase et al [13] further studied the effect of Zn-doped CuMo 0.94 W 0.06 O 4 on the phase transition and thermochromism properties.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave dielectric ceramics have been extensively used as key materials in dielectric resonators, filters, antennas, strip lines, and phase shifters for reasons of low cost, stability, efficiency, and ease of use . Recently, to meet the increasing demands for miniaturization and integration, low‐temperature cofired ceramics (LTCC) technology has become crucial due to its ability to integrate a versatile mix of passive microwave components to fabricate highly integrated multichip modules . These ceramics must fulfill the requirement of lower sintering temperatures than the melting point of the inner metal electrode such as Ag (961°C), along with the appropriate relative permittivities (ε r ), high‐quality factors ( Q × f ), and temperature stability .…”
Section: Introductionmentioning
confidence: 99%
“…The positive charge developed at complex b and c is anticipated to be stabilized by the nanocluster. [22] The catalyst is recyclable without loss of activity and the HRMS-ESI experiment reveals that there is no leachingo fc atalystd uring the reaction (see the Supporting Information).…”
mentioning
confidence: 99%
“…In this context,w eh ave used this CuMoO 4 bimetalic nanocatalyst for the CÀSc ross-coupling reaction. [22] We first investigated the reaction of iodobenzene 1a with benzenethiol 2a in acetonitrile solventa tr oomt emperature in the presenceo f2 .6 mol %o fC uMoO 4 nanoparticle and 1.2 equivalents of Cs 2 CO 3 ( Table 1, entry 1). The reactiona fforded 80 %C ÀSc ross-coupled product 3a after 12 h. Solvents like tBuOH, toluene, and 1,4-dioxane underwentn or eaction after 12 h( entries 2-4).…”
mentioning
confidence: 99%